Rapid detection of influenza A virus infection utilizing an immunomagnetic bead-based microfluidic system() - Lien, Kang-Yi (Biosens Bioelectron, 2011)
This study reports a new immunomagnetic bead-based microfluidic system for the rapid detection of influenza A virus infection by performing a simple two-step diagnostic process that includes a magnetic bead-based fluorescent immunoassay (FIA) and an end-point optical analysis. With the incorporation of monoclonal antibody (mAb)-conjugated immunomagnetic beads, target influenza A viral particles such as A/H(1)N(1) and A/H(3)N(2) can be specifically recognized and are bound onto the surface of the immunomagnetic beads from the specimen sample. This is followed by labeling the fluorescent signal onto the virus-bound magnetic complexes by specific developing mAb with R-phycoerythrin (PE). Finally, the optical intensity of the magnetic complexes can be analyzed immediately by the optical detection module. Significantly, the limit of detection (LOD) of this immunomagnetic bead-based microfluidic system for the detection of influenza A virus in a specimen sample is approximately 5 × 10(−4) hemagglutin units (HAU), which is 1024 times better than compared to conventional bench-top systems using flow cytometry. More importantly, the entire diagnostic protocol, from the purification of target viral particles to optical detection of the magnetic complexes, can be automatically completed within 15 min in this immunomagnetic bead-based microfluidic system, which is only 8.5% of the time required when compared to a manual protocol. As a whole, this microfluidic system may provide a powerful platform for the rapid diagnosis of influenza A virus infection and may be extended for diagnosis of other types of infectious diseases with a high specificity and sensitivity.